Association of serum syndecan-1 concentrations with albuminuria in type 2 diabetes - Kakutani, Yoshinori; Morioka, Tomoaki; Yamazaki, Yuko; Ochi, Akinobu; Fukumoto, Shinya; Shoji, Tetsuo; Emoto, Masanori (Diabetes & vascular disease research, 2024)
Introduction Syndecan (SDC)-1 is a transmembrane heparan sulfate proteoglycan and is a major component of endothelial glycocalyx (EG). This study aimed to investigate the association of serum SDC-1 concentration as a marker of EG degradation with albuminuria in type 2 diabetes. Methods We included 370 patients with type 2 diabetes and 219 individuals with no diabetes. The individuals with estimate glomerular filtration rate <30 mL/min/1.73 m2 were excluded. Results Serum SDC-1 concentration was higher in type 2 diabetes than in no diabetes. The presence of diabetes was independently associated with log [SDC-1] in multivariate analysis. In type 2 diabetes, serum SDC-1 concentration was correlated with log [urinary albumin-to-creatinine ratio (ACR)]. Moreover, log [SDC-1] was an independent determinant of log [ACR] after adjustment for known risk factors of albuminuria. Conclusions Serum SDC-1 concentration was higher in patients with type 2 diabetes compared to individuals with no diabetes and an independent determinant of ACR. This study implicates the role of the EG degradation in albuminuria in type 2 diabetes.